2018
DOI: 10.20448/2002.22.79.90
|View full text |Cite
|
Sign up to set email alerts
|

Does International Financial Reporting Standards (IFRS) Impact Profitability Ratios of Listed Banks in Nigeria?

Abstract: This study provides an empirical analysis of the impact of IFRS on profitability ratios of eleven (11) banks in Nigeria. The study addresses the research hypotheses by comparing the key profitability ratios computed under the Pre-IFRS for three year period from 2009-2011 and three year period from 2013-2015 under the Post-IFRS regime. The study used Wilcoxon Signed Rank test and Normality test as a statistical method to analyze the data. The findings revealed that IFRS adoption has not produced any meaningful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…According to Cohen, .1=small effect, .3=moderate effect, and .5=large effect. This technique was used in the study of Erin et al (2018) when determining the pre and post-impact of IFRS on the profitability of listed companies.…”
Section: Descriptive Statistics Summarymentioning
confidence: 99%
“…According to Cohen, .1=small effect, .3=moderate effect, and .5=large effect. This technique was used in the study of Erin et al (2018) when determining the pre and post-impact of IFRS on the profitability of listed companies.…”
Section: Descriptive Statistics Summarymentioning
confidence: 99%
“…Although the importance of financial literacy on the financial performance of MSMEs is well-documented and evidenced, a significant number of entrepreneurs lacked the financial knowledge, attitudes, and behaviors required to increase their business profitability, liquidity, and how to effectively make use of debt (leverage) to undertake better investments or projects (Pakovic et al, 2018). Erin et al (2017) noted that one of the reasons why entrepreneurs make poor, inappropriate, unprofessional, and undesirable financial decisions is due to the absence or deficiency of financial knowledge, attitudes, and behaviors, as well as inadequate time to learn about the basic concepts of financial literacy. Ernest (2018) further argued that these poor financial decisions undermine entrepreneurial activity, manifested in poor business profitability, insufficient liquidity, and the accumulation of too many business debts with no successive repayment plans.…”
Section: Relationship Between Financial Literacy and Financial Perfor...mentioning
confidence: 99%
“…Moreover, Tumba et al (2021) found that financial literacy has a significant relationship with financial performance because it is a vital indicator of success in managing the affairs of small business operations in the present complex and rapidly changing business environment. This is vital given that there is evidence showing that one of the reasons why entrepreneurs make poor, inappropriate, unprofessional, and undesirable financial decisions is due to the absence or deficiency of financial knowledge, attitude, and behaviors, as well as inadequate time to learn about the basic concepts of financial literacy (Erin et al, 2017). Consequently, higher levels of financial literacy promote better financial performance, thereby providing opportunities for better planning of future life events for entrepreneurs like retirement, buying a house, or savings for children's education (Owolabi et al, 2021).…”
Section: Fpmentioning
confidence: 99%
“…Nigeria's leading private sector companies, particularly banks, voluntarily adopted IFRS in 2010. It is expected that the adoption of IFRS would reduce earnings variability and improve accounting quality (Erin, Olayinka & Adedayo, 2019;Tanko, 2012). It will reduce information asymmetry and would subsequently smoothen communications among managers, shareholders, creditors and other interested parties (Erin, Olayinka & Adedayo, 2019;Bushman & Smith, 2001), resulting in lower agency costs (Healy & Palepu, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that the adoption of IFRS would reduce earnings variability and improve accounting quality (Erin, Olayinka & Adedayo, 2019;Tanko, 2012). It will reduce information asymmetry and would subsequently smoothen communications among managers, shareholders, creditors and other interested parties (Erin, Olayinka & Adedayo, 2019;Bushman & Smith, 2001), resulting in lower agency costs (Healy & Palepu, 2001). Lower information asymmetry would also lead to lower costs of equity and debt financing (Guermazi, 2022;El-Gazzar et al, 1999;Botosan & Plumlee, 2002).…”
Section: Introductionmentioning
confidence: 99%